ANALISIS PERBANDINGAN POTENSI DAN REALISASI PENERIMAAN PAJAK RESTORAN TAHUN 2014-2017 (STUDI PADA BADAN KEUANGAN KABUPATEN MINAHASA UTARA) - Waworundeng, Veronica; Elim, Inggriani; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The purpose of study aims to determine the growth of restaurant tax revenues and analyze the potential and realization of restaurant tax revenues in Kabupaten Minahasa Utara. The data used to analyze that is qualitative data, the source using primary and secondary data. Data collection methods used in this study descriptive analysis method, which aims to explain about the object. The result of the research shows that the realization of restaurant tax is big enough compared to the potential of restaurant tax revenue. The effectiveness shows its effective.Keywords: Restaurant Tax, Restaurant Tax Potential, Restaurant Tax Reception and Restaurant Tax Effectiveness